Motives of Student Teachers in Academic Teacher Education for Secondary Education: Research in Flanders (Belgium) on the Motivation to Become and to Remain a Teacher - Katho Pauwels; Helena Van Loon; Els Tanghe; Wouter Schelfhout (MDPI AG, 2022)
The increasing shortage of teachers in secondary education, in Flanders (Belgium) as well as worldwide, is partly due to an insufficient inflow of new teachers. This stimulates research on the motivation of students to become and remain teachers. Our research focuses on the motives of student teachers in academic teacher education for secondary education to become a graduated teacher and how this evolves during teacher education, taking into account different profiles of students. Surveys, with closed and open questions based on our theoretical framework, were conducted at different points in time during teacher education as a basis for mixed method analyses. Compared to the period between the start and the end of the teacher education courses, it appeared that graduated student teachers attached more importance to the motives 'subject orientation' and 'educational orientation'. The research shows a shift to a more realistic educational orientation among graduated students. 'Work dynamic' aspects as a motive to work in education were generally considered equally important by women and men but combination possibilities were more important for men. Specifically related to students with a 'teacher in training' [TiT] statute, graduated TiT-students considered the motive 'idealism' more important than non-TiT-students. Related to working students, 'work perspective' appeared to be more important compared to non-working students. These insights into the evolving motives of student teachers have a number of possible implications for the organization of teacher education, which can also contribute to reducing the teacher shortage. Teacher education can put extra emphasis on positive and qualitative hands-on experiences by performing a well-considered selection of internship schools and mentors. At the same time, teacher education can offer even more space and time for student teachers to dedicate to internships, by keeping other activities such as deadlines and teaching moments during internships to a minimum.